Man's role in the changing habitat of Mema under the old Kingdom of Ghana - Haaland, G. (International Livestock Centre for Africa, 1979)
Summary and interpretation of the findings of an archaeological investigation of the Mema area of central Mali, particularly. effect of human activities specially iron smelting and subsistence farming on the present environment feature of the area.